The Role of Digital Islamic Economy in Increasing Financial Inclusion in the Fintech Era - yulia, Devi; Vidiati, Cory; Nursindi, Mita (Advances In Social Humanities Research, 2024)
This research aims to explore the role of digital Islamic economics in increasing financial inclusion, with a focus on the use of sharia fintech in countries with a majority Muslim population. With a qualitative approach through literature studies, this study identifies how financial technologies that are in line with the principles of Islamic economics can expand access to fair and inclusive financial services. Research findings show that sharia-based fintech, such as sharia microloans, contribute significantly to people's economic empowerment, reduce economic inequality, and encourage greater participation in the digital economy, especially among women and youth. However, challenges related to regulation and understanding of technology are obstacles that need to be overcome. This study provides recommendations for the development of policies that support sharia fintech and strengthen digital literacy among the community. The results of this study are expected to provide guidance for policymakers and fintech companies in designing more inclusive services.